Uganda : Poverty Reduction Strategy Paper: Progress Report. (IMF Staff Country Reports; Country Report ;, 2014)
This Poverty Reduction Strategy Paper on Uganda discusses that the National Development Plan (NDP), Uganda's current Poverty Reduction Strategy Paper, was introduced in 2010/11 and originally intended to cover five fiscal years, until 2014/15. The NDP emphasises the need to accelerate economic growth to create jobs, increase average income and provide the financial resources required to expand public investment and service delivery. However, several macroeconomic and implementation challenges have reduced infrastructure investment, economic growth and job creation below the levels targeted by the plan. The key strategic objectives of the plan will be maintained over the next two years, with focus placed on strengthening public investment management, creating fiscal space for infrastructure projects and enhancing the development of practical skills among the labour force. The recalibrated macroeconomic framework outlined in Section IV will help guide fiscal policy and economic management as the next National Development Plan is being finalised. NDP II will be launched before the 2016/17 fiscal year and will guide budgetary priorities and programmes over the medium term.